Körper - Waltz, Sacha (2000)
Berlin-based dance-maker and tanztheater luminary Sasha Waltz is celebrated for her compelling imagery and body-focused choreography. Taking the body itself as her subject in Körper, Waltz combines clinical analysis and fantastical illusions as 13 dancers meld together to form strange chimerical creatures and squirm behind glass like scientific specimens, in a series of living tableaux.